2020
DOI: 10.1029/2019ja027317
|View full text |Cite
|
Sign up to set email alerts
|

Common‐Volume Dual‐Frequency Radar Observations of 150‐km Echoes and Implications

Abstract: We present and discuss common-volume dual-frequency radar observations of 150-km echoes made at 30 and 53 MHz from Gadanki by employing identical transmitter power and antenna beam width. These controlled experiments reveal that 150-km echoes are stronger, broader in spectral width, and more frequent in their occurrence at 30 MHz than at 53 MHz. Echo intensities at 30 and 53 MHz are found to be consistent with the rocket-borne observations of wave number spectrum of meter-scale irregularities in the 150-km reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Just off perpendicular to B , ion spectra reveal broad frequency enhancements and significant power in the ion line, especially for longer wavelengths. This is consistent with observations of 150 km echoes, which have been show to have more backscattered power for 30 MHz radars than 50 MHz (A. Patra et al., 2020; A. K. Patra et al., 2020). It also provides some evidence for the lack of observations of 150 km echoes at ALTAIR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Just off perpendicular to B , ion spectra reveal broad frequency enhancements and significant power in the ion line, especially for longer wavelengths. This is consistent with observations of 150 km echoes, which have been show to have more backscattered power for 30 MHz radars than 50 MHz (A. Patra et al., 2020; A. K. Patra et al., 2020). It also provides some evidence for the lack of observations of 150 km echoes at ALTAIR.…”
Section: Discussionsupporting
confidence: 91%
“…There are two populations of 150 km echoes, Naturally Enhanced Incoherent Scatter (NEIS), or Type‐A, which have a typical signal‐to‐noise ratio (SNR) of around 5 dB, and Field Aligned Irregularities (FAIs), or Type‐B, which can have a SNR of around 20 dB (Chau & Kudeki, 2013; A. Patra et al., 2020; A. K. Patra et al., 2020). NEIS accounts for the majority of observations of 150 km echoes and is primarily observed by Jicamarca Radio Observatory (JRO) as it is the most sensitive (Chau & Kudeki, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic simulations in Oppenheim and Dimant (2016) showed that this mode conversion does occur in a photoelectron‐driven instability, but the exact mechanism is unknown. The weak turbulence theory may explain this mode conversion, and a wavenumber matching condition in weak turbulence theory could also explain the lack of observations at the higher frequency ALTAIR radar (Forme, 1999; Nicholson, 1983), as well as concurrent observations at 30 and 50 MHz from the Gadanki radar (Patra et al, 2020).…”
Section: Discussion and Summarymentioning
confidence: 97%
“…Observationally, 150‐km echoes have only been observed by radars with transmit frequencies in the range of 30–50 MHz (Kudeki & Fawcett, 1993; Patra, Chaitanya, Rao, & Kamaraj, 2020). Notably, the ALTAIR radar (150 MHz) has never observed 150‐km echoes despite its favorable location at the equator (Chau et al., 2023).…”
Section: Application To 150‐km Echoesmentioning
confidence: 99%